The Perspective of Nectarine Fruit as a Sugar Substituent in Puddings Prepared with Corn and Rice Starch - Dasha Mihaylova (MDPI AG, 2021)
It has been long recognized that fruits are healthy diet compounds as they are excellent sources of health-beneficial bioactive components (polyphenols, minerals, vitamins, organic acids, etc.). The diversification of the consumer’s taste calls for an expansion of food options and novel ingredients. Puddings are a well-known food choice introduced in the human diet at a very early age because of their easy and high digestion. Four formulations with two types of starch (corn and rice) were selected as object of analysis. Nectarines were incorporated as a purée, and lyophilized powder. The nectarine variety “Gergana”, used for the preparations, is a local variety with proven beneficial properties. The study aimed at analyzing the physical (moisture, ash, color, water-holding capacity, water activity, density and syneresis), textural (firmness, gumminess, cohesiveness, springiness, and chewiness), nutritional, and sensory characteristics of the nectarine-enriched puddings. The outcomes obtained from this study provided significant information about the possible application of the formulations in the children’s daily menus. All four formulations had distinct peachy aroma. The formulations prepared with nectarine purée resulted in a better sensory perception about their texture, and better water-holding capacity. At this point, the formulation prepared with lyophilized fruit and rice starch has the most promising results. Sufficient evidence leads to further exploration of the perspective of fruit-enriched puddings in order to improve their technological and health-promoting properties.